Size distribution and volume fraction of T1 phase precipitates from TEM images: Direct measurements and related correction. (November 2015) - Dorin, Thomas; Donnadieu, Patricia; Chaix, Jean-Marc; Lefebvre, Williams; Geuser, Frédéric De; Deschamps, Alexis
Highlights: A size correction method that accounts for the TEM foil thickness is presented. To optimise the correction, no less than 9 size classes and no more than 13 are used. The T1 precipitate size and volume fraction was successfully obtained from STEM. The T1 volume fraction was confirmed with Atom probe measurements. Abstract: Transmission Electron Microscopy (TEM) can be used to measure the size distribution and volume fraction of fine scale precipitates in metallic systems. However, such measurements suffer from a number of artefacts that need to be accounted for, related to the finite thickness of the TEM foil and to the projected observation in two dimensions of the microstructure. We present a correction procedure to describe the 3D distribution of disc-like particles and apply this method to the plate-like T1 precipitates in an Al–Li–Cu alloy in two ageing conditions showing different particle morphologies. The precipitates were imaged in a High-Angular Annular Dark Field Microscope (HAADF-STEM). The corrected size distribution is further used to determine the precipitate volume fraction. Atom probe tomography (APT) is finally utilised as an alternative way to measure the precipitate volume fraction and test the validity of the electron microscopy results.